Influence and Comparison of Various Hydroxyapatite Based Bone Grafts Fabricated and Used in Bone Fracture Unions: An In Vivo Study - Kom, Mustafa; Aksakal, Bunyamin; Demirel, Mehtap; Malkoc, Melih (Amer Scientific Publishers, 2015)
Hydroxyapatite (HA) based biografts were fabricated and used in bone fracture treatments and bone unions and the effects of fabricated biografts on bone tissue was evaluated. Biografts are produced via sol gel method by additions of varying amounts of CaO, Na2CO3, KH2PO4 and Yttria into HA. The fabricated grafts were characterized by SEM, XRD, three point bending (3PB) tests. In order to evaluate the influence of fabricated grafts on bone generation and union, the fracture defects were created in left tibias of New Zealand rabbits and the grafts were filled into these defects and analyzed through in vivo study. At the end of eight weeks, after sacrifizing the bone union and healing are compared via radiologic, mechanical and histopathologic analysis. Similar results in mechanical, morphological, biocompatibility properties were determined between the fabricated HA based grafts and a commercial graft. It was observed that Yttria and CaO addition into HA caused an increase in density and enhanced mechanical properties when compared to the rest of samples, however, H30 biograft provided better union and bone formation in the defected regions created on rabbit tibias.
Keywords: Hydroxyapatite; Bone; Fracture; Union